As relações humanas na escola: fundamentos epistemológicos e ontológicos para uma interdisciplinaridade na educação - Fernandes, Peterson José Cruz (2014)
This qualitative research with interdisciplinary intervention through literature review, experiences and dialogues, aimed to study and reflect on the relationship between school and interdisciplinarity, evidencing its base: human relationships based on intersubjectivity, excessively punished today. Based on this discussion, we tried to find grounds for the construction of an interdisciplinary school that critic the mechanisms that make us less people and at the same time, contributes to the development of competent people to a life that is not there, but, coexistence. There was here, the desire to take care of human relationships in school. In this research it was possible to notice that the contemporary, the result of a project that fundamentally shifted the reason for systemic and strategic fields, has presented challenges for humans and a sustainable life on the planet, because, among several consequences, promoted a dichotomy between science and existence. The maximum Cartesian: I think therefore I am, annihilated the know thyself. A reflection of this reality: companies, projects, policies, and especially people, are often forced to forget the being, giving way to other verbs too. Thus, there is the need to build subsidies that would allow a more humane and humanizing new path that would bring back man and science, returning them to their proper places. The school has an important role in this process because it is a fruitful space for reflection and action. The interdisciplinarity, understood in this work from the interdisciplinary practice of Ivani Catarina Arantes Fazenda, presents itself as full horizon of meaning, its epistemological and ontological potential, which understands that it is through and for man and the world that the educational process must exist, and in these instances, their territory more legitimate sense. This interdisciplinarity, inserted in a space that is constantly changing and in construction by five principles - consistency, humbleness, wait, respect and detachment, proposes to overcome the dichotomy between science and existence, and the replacement of truth by the truth of science the man as being in the world and the world, bringing up the context so urgent. It is also possible for the coexistence of reason and feeling; perception and knowledge. It is the reconsideration of a unitary conception of man and multiple world